Microbiome-Mediated Upregulation of MicroRNA-146a in Sporadic Alzheimer’s Disease - Zhao, Yuhai; Lukiw, Walter J. (Frontiers in Neurology, 2018)
The first indication of a potential mechanistic link between the pathobiology of the human gastrointestinal (GI)-tract microbiome and its contribution to the pathogenetic mechanisms of sporadic Alzheimer’s disease (AD) came a scant 4 years ago.* Ongoing research continues to strengthen the hypothesis that neurotoxic microbial-derived components of the GI tract microbiome can cross aging GI tract and blood-brain barriers and contribute to progressive pro-inflammatory neurodegeneration, as exemplified by the AD-process. Of central interest in these recent investigations are the pathological roles played by human GI tract resident Gram-negative anaerobic bacteria and neurotropic viruses – two prominent divisions of GI tract microbiome-derived microbiota - which harbor considerable pathogenic potential. It is noteworthy that the first two well-studied microbiota - the GI tract abundant gram-negative bacteria Bacteroides fragilis (B. fragilis) and the neurotropic herpes simplex virus-1 (HSV-1) both share a final common pathway of NF-kB (p50/p65) activation and microRNA-146a induction with ensuing pathogenic stimulation of innate-immune and neuro-inflammatory pathways. These appear to strongly contribute to the inflammation-mediated amyloidogenic neuropathology of AD. This communication: (i) will review recent research contributions that have expanded our understanding of the nature of the translocation of microbiome-derived neurotoxins-across biophysiological barriers; (ii) will assess multiple-recent investigations of the induction of the pro-inflammatory pathogenic microRNA-146a by these two prominent classes of human microbiota; and (iii) will discuss the role of molecular neurobiology and mechanistic contribution of polymicrobial infections to AD-type neuropathological change.